Legal Protection for Hajj Pilgrims Through Regional Regulation - Hamzani, Achmad Irwan; Siswanto, Siswanto; Aravik, Havis (IAIN Samarinda, 2018)
The Law on the Conduct of Hajj Pilgrimage mandates the management of the Hajj pilgrimage is organized by the government. This management includes the coaching, service, and protection of the pilgrims from Indonesia, in Saudi Arabia, to returning to the homeland. This law also stipulates that the authority to conduct Hajj pilgrimage management is not only vested to the Ministry of Religious Affairs but also may involve the local government. This article aims to look at the role of local governments in providing service assistance and legal protection to the conduct of Hajj pilgrimage by means of regional regulations or bylaws. Using a normative approach, this article analyzes the extent to which the importance of bylaws in helping implement services for pilgrims. The results of this study confirm that there are 3 important arguments for why the local government must issue regional regulations to provide legal services and protection for pilgrims. First, philosophically, the pilgrimage journey does not depart from Jakarta only, but through the origin area which is still in the corridors of power of the local government. Second, sociologically, it is a form of the local government responsibility to the local people who perform the Hajj pilgrimage. Third, juridically, bylaws should regulate technical matters in order to provide optimal service in the conduct of the Hajj pilgrimage which is pursuant to the Law and regulations on Hajj pilgrimage in Indonesia.Keywords: legal protection, hajj pilgrims, regional regulation.AbstrakUndang-Undang penyelenggaraan ibadah haji mengamanatkan pengelolaan pelaksanaan ibadah haji yang meliputi pembinaan, pelayanan, dan perlindungan jamaah haji semenjak dari tanah air, di Arab Saudi, hingga kembali ke tanah air. Undang-undang ini juga memerintahkan kewenangan pelayanan masalah haji tidak hanya pada kementerian Agama, namun boleh melibatkan pemerintah daerah. Artikel ini bertujuan untuk melihat peran pemerintah daerah dalam memberikan bantuan layanan dan perlindungan hukum melalui peraturan daerah. Dengan menggunakan pendekatan normatif, artikel ini menganalisis sejauh mana pentingnya peraturan daerah menjadi peraturan di tingkat daerah dalam membantu melaksanakan pelayanan terhadap jamaah haji. Hasil dari artikel ini menegaskan bahwa terdapat 3 argumen penting mengapa Pemerintah Daerah harus mengeluarkan peraturan daerah guna memberikan pelayanan dan perlindungan hukum bagi jamaah haji. Pertama, secara filosofis perjalanan ibadah haji tidak berangkat dari Jakarta, tetapi melalui daerah asal yang masih dalam koridor pemerintah daerah. Kedua, Kedua, secara sosiologis sebagai bentuk tanggung jawab Pemerintah Daerah kepada masyarakat daerah yang menunaikan ibadah haji. Ketiga, secara yuridis PERDA mengatur secara teknis dalam rangka memberikan pelayanan yang optimal dalam penyelenggaran ibadah haji sesuai dengan Undang-Undang Republik Indonesia Nomor 13 Tahun 2008 tentang Penyelenggaraan Ibadah Haji dan Peraturan Pemerintah Republik Indonesia Nomor 79 Tahun 2012 tentang Pelaksnaan Undang-Undang Republik Indonesia Nomor 13 Tahun 2008 tentang Penyelenggaraan Ibadah Haji.Kata kunci: perlindungan hukum, ibadah haji, peraturan Daerah